Hubungan Dukungan Keluarga Dengan Kepatuhan Pasien Kanker Payudara Menjalani Kemoterapi Di Rsud Dr. H. Abdul Moeloek - Setiawati, Octa Reni; Roza, Ghina Efrilia (Universitas Islam Negeri Raden Intan Lampung, 2019)
Breast cancer is the most common type of cancer experienced by women in the world and is also the type of cancer that is the leading cause of death in women. One type of treatment that can be used in the treatment of breast cancer is chemotherapy. Chemotherapy is a type of treatment to kill or slow down the growth of cancer cells which requires a long period of time, where in this treatment required compliance. Adherence in chemotherapy can be influenced by several factors, one of which is family support. To find out the relationship between family support and breast cancer patient's compliance undergoing chemotherapy at RSUD Dr. H. Abdul Moeloek Lampung Province. Analytical observational research with a retrospective approach. The sampling technique is done by accidental sampling. Obtained data from 120 samples that filled out family support questionnaires and medical records of patients undergoing chemotherapy at RSUD Dr. H. Abdul Moeloek, Lampung Province, which has good family support of 101 people (84.2%) and 108 patients (90.0%) are obedient to chemotherapy. Kendall-tau test results obtained a significance value of 0.000 which indicates that there is a significant relationship between family support and breast cancer patients adherence undergoing chemotherapy. There is a significant relationship between family support and breast cancer patient compliance undergoing chemotherapy with a correlation coefficient of 0.607 and a significance value of 0.000.